The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1017/s1368980022000143
|View full text |Cite
|
Sign up to set email alerts
|

The performance of mid-upper arm circumference for identifying children and adolescents with overweight and obesity: a systematic review and meta-analysis

Abstract: Objective: This study aimed to synthesize the existing evidence on the performance of Mid-Upper Arm Circumference (MUAC) to identify children and adolescents with overweight and obesity. Design: Systematic review and meta-analysis. Setting: We searched PubMed, EMBASE, SCOPUS, Cochrane Library, Web of Science, CINAHL, and Google scholar databases from their inception to December 10, 2021, for relevant studies. There were no restrictions regarding the language of publicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 50 publications
(73 reference statements)
0
11
0
Order By: Relevance
“…MUAC can serve as a valuable screening and surveillance tool in situations where measuring weight is considered inappropriate due to concerns about body image issues 10 . Studies have proposed that MUAC can be used as an alternative tool for identifying children and adolescents with overweight and obesity at both clinical and community levels 9,11 …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…MUAC can serve as a valuable screening and surveillance tool in situations where measuring weight is considered inappropriate due to concerns about body image issues 10 . Studies have proposed that MUAC can be used as an alternative tool for identifying children and adolescents with overweight and obesity at both clinical and community levels 9,11 …”
Section: Introductionmentioning
confidence: 99%
“…10 Studies have proposed that MUAC can be used as an alternative tool for identifying children and adolescents with overweight and obesity at both clinical and community levels. 9,11 A recent systematic review and meta-analysis has demonstrated that MUAC performs excellently in identifying adolescents with obesity, as defined by BMI Z-score. 11 The review also highlights studies that have compared the performance of MUAC with BMI Z-score and bioelectrical impedance.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…4,5,6,7 However, this has not been the case in middle-income countries, where there is scanty literature related to the phenomenon under study. In South Africa, although there has been a high prevalence of overweight and obesity amongst children, 8,9,10,11 there are few research studies regarding the relationship between physical fitness and body composition amongst primary school learners.…”
Section: Introductionmentioning
confidence: 99%